Novel electroless process for copper coating of flyash using titania/ultraviolet-radiation/metal catalyst-system - Shijitha, T.; Baiju, K. V.; Shukla, S.; Patil, K.; Warrier, K. G. K. (Applied Surface Science, 2009)
A novel electroless process has been demonstrated in this investigation to coat the surface of flyash particles with a conducting metal such as copper. The conventional electroless process has been modified for this purpose by replacing the tin-palladium catalyst-system with the titania/ultraviolet-radiation/metal catalyst-system, where the metal is either copper or silver as demonstrated here. The mechanism of copper coating of flyash particles in an electroless bath, using the novel methods of surface-sensitization and surface-activation, has been systematically studied by monitoring changes in the surface-morphology, surface-chemistry, and surface-structure of flyash particles using the scanning electron microscope, energy dispersive analysis of X-rays, X-ray photoelectron spectroscope, and X-ray diffraction. It has been revealed that the novel electroless method involves coating the flyash particles with titania photocatalyst via sol-gel, which acts as a surface-sensitizer under the ultraviolet-radiation exposure for the subsequent surface-activation with the copper- or silver-clusters. The latter in turn acts as surface-catalyst for the subsequent Cu-coating in an electroless bath. The proposed mechanism of surface-sensitization and surface-activation of flyash particles using the novel catalyst-system has been compared with that using the conventional catalyst-system. (C) 2009 Elsevier B. V. All rights reserved.
Keywords: Copper; Electroless; Flyash; Photocatalysis; sol-gel; titania